Bali is the best holiday destination: â€œBarack Obama Approvedâ€ - Ida Ayu Putu Widya Indah Sari (Bali Tourism Board, 2017)
Bali is getting famous, It is related to the plan of former President of the United States Barack Obama to visit Bali for vacation with his family. He scheduled to spend his vacation in Bali with his family for five days from June 23rd to 28th. Before the group are heading to Yogyakarta. Related to the security, Hundreds of police and TNI officers stand guard along the road as far as 40 km to secure the departure of Barack Obama's entourage to Yogyakarta. there was no airport closure when Obama's plane took off. However, he said there was indeed a priority given for the plane to take off, both on arrival and departure of the entourage.